Meningkatkan efektifitas digital bank syariah - Prasetyo Utomo, Mahesa Dwi (Maliki Interdisciplinary Journal, 2024)
This article analyzes the digital market potential of Islamic banks, marketing challenges, and effective management strategies. Key aspects examined include competition with conventional banks, customer trust in online transactions, and the use of social media as a primary marketing tool. SEO optimization and content strategy are also described as ways to enhance online visibility. Monitoring and analysis of marketing data provide valuable insights for optimizing marketing efforts. By combining these elements, Islamic banks can strengthen their position in the competitive digital banking industry. This article employs a qualitative research method with a literature study approach. In conclusion, a meticulous digital marketing strategy focused on Sharia principles is the key for Islamic banks to succeed in the ever-evolving digital era.